OC-017 A Discriminant Analysis Demonstrates that Siblings of Patients with Crohn'S Disease have a Distinct Microbiological and Immune Phenotype Compared with Healthy Controls: Insights into Disease Pathogenesis. (4th June 2013) - Hedin, C; McCarthy, N E; Louis, P; Farquharson, F; McCartney, S; Taylor, K; Prescott, N; Murrells, T; Stagg, A J; Whelan, K; Lindsay, J O
Abstract : Introduction: Crohn's disease (CD) is associated with genetic risk, intestinal dysbiosis, altered blood T-cell phenotype, increased faecal calprotectin (FC) and intestinal permeability (IP). Factors shared by CD patients and unaffected siblings may be implicated in CD pathogenesis. Aims: Delineate the genetic, immune and microbial phenotype of patients, siblings and healthy controls (HC); identify factors associated with CD that discriminate siblings from HC. Methods: Faecal microbiota, FC, blood T-cell phenotype, IP and genotype risk over 72 CD risk loci, were measured by qPCR, ELISA, flow cytometry, sugar permeability and Illumina Bead Array respectively, in 22 patients with inactive CD, 21 of their healthy siblings and 25 HC. Results: In addition to genotype risk, siblings shared aspects of the phenotype of CD patients, distinct from HC, as previously reported.1 Direct discriminant function analysis revealed that the variables maximally separating siblings from HC (Function 2) were: increased β7 integrin expression by circulating naïve CD4+ T-cells and an increased proportion of memory CD4+ T-cells as well as reduced faecal Roseburia spp. (Image 1). In contrast, the variables differentiating CD patients from HC (Function 1) were: elevated FC and altered faecal microbiota (reduced Faecalibacterium prausnitzii, Cluster IV Ruminococcus spp. Bacteroides-Prevotella and Clostridial cluster IV). Conclusion: Healthy siblings of CD patients manifest immune and microbiological abnormalities associated with CD, distinct from their genetic risk. Unaffected siblings of CD patients are an excellent model in which to investigate early CD pathogenesis. Disclosure of Interest: None Declared Reference: Hedin et al. Gut 2012; 61: Suppl. 2 A22-A23.